Prognostic impact of neoadjuvant chemotherapy in patients with synchronous colorectal liver metastasis: A propensity score matching comparative study. (October 2021) - Ueno, Masaki; Komeda, Koji; Kosaka, Hisashi; Nakai, Takuya; Nomi, Takeo; Iida, Hiroya; Tanaka, Shogo; Ikoma, Hisashi; Matsuda, Kenji; Hirokawa, Fumitoshi; Matsumoto, Masataka; Hokuto, Daisuke; et al.
Abstract: Background: Synchronous colorectal liver metastasis (SCRLM) is at an advanced tumor stage and requires multidisciplinary treatments. Neoadjuvant chemotherapy (NAC) is thought to be an effective treatment modality, but its prognostic impact is still unclear. Materials and methods: Patients with resectable SCRLM presented to eight university hospitals between 2007 and 2017 were retrospectively reviewed. Propensity score matching (PSM) was performed to adjust baseline characteristics between patients who received NAC with those who underwent up-front hepatectomy. The prognostic impact of NAC was then evaluated. Results: The cohort comprised of 320 patients: 151 patients received NAC and the remaining 169 patients underwent up-front hepatectomy. After a 1:1 ratio of PSM, 102 patients per group were selected. Within the PSM cohort, 66% patients had multiple liver tumors, with 15% having five or more liver tumors. The median survival (95% confidence interval) periods for patients with and without NAC in the PSM cohort were 88.5 (68.4 – not reached) and 84.2 (52.1 – not reached) months, respectively ( P  = 0.51). On multivariate analysis, the postoperative events in these patients including operative complications and use of adjuvant chemotherapy after hepatectomy were prognostic factors with hazards (95% confidence interval) being 1.88 (1.18–2.98) and 0.65 (0.42–1.01), respectively. Conclusion: This PSM study was restricted to patients with SCRLM and relatively advanced tumor stagings. NAC did not show any significant prognostic impact. While operative complications had a significant prognostic impact, use of adjuvant chemotherapy after hepatectomy had only a marginal prognostic impact. Reconsideration of indications for NAC is needed. Highlights: Neoadjuvant chemotherapy (NAC) is thought to be an effective treatment modality for synchronous colorectal liver metastasis (SCRLM). The prognostic impact is unclear due to biased baseline patient characteristics between those with and without NAC. We performed propensity score matching (PSM) analysis on patients with resectable SCRLM to evaluate the prognostic effect of NAC. NAC did not show significant prognostic impact, even in the PSM cohort.